Hubungan Pengetahuan dan Sikap Ibu dengan Perilaku Pencegahan Stunting pada Balita di Posyandu Tunas Mekar 1 Kelurahan Krukut, Depok - Zahrotul Mutingah (2021)
Stunting is a problem of malnutrition that is still experienced by toddlers throughout the world, including Indonesia. In reducing the prevalence of stunting, preventive behavior is needed. A person's behavior can be influenced by his knowledge and attitude. The purpose of this study was to determine the relationship between knowledge and attitudes of mothers with stunting prevention behavior in toddlers at Posyandu Tunas Mekar 1 Krukut Village, Depok. The method used in this research is quantitative with a cross-sectional design. Sampling used a total sampling technique with 74 samples. Collecting data used a questionnaire sheet that had been tested for validity and reliability. The questionnaire is divided into three parts, namely knowledge, attitudes, and stunting prevention behavior. The results of the Spearman Correlation test showed that there was no relationship between knowledge and stunting prevention behavior (p-value= 0.100), but there is a relationship between attitudes and stunting prevention behavior (p-value= 0.001). In the mother's characteristic variable, it was found that there was a relationship between mother's work and stunting prevention behavior (p-value= 0.003), but there was no relationship between maternal age (p-value =0.305) and mother's education (p-value= 0.053) with stunting prevention behavior.